Ideal Illumination for Smartphone-based Trabeculectomy Bleb Photography - Gagan Kalra; Parul Ichhpujani; Sahil Thakur; Urvashi Sharma (Journal of Ophthalmic & Vision Research)
Abstract Purpose: Ophthalmology has seen numerous novel uses for smartphones over the years including fundus photography, telemedicine, and operative videography. However, anterior segment photography for assessing and documenting trabeculectomy bleb morphology using a smartphone has not been explored in detail. With the current study, we aim to characterize ideal illumination for the anterior segment smartphone photography in trabeculectomy patients. Methods: Thirty status post-trabeculectomy patients were enrolled in this study. Native camera application and FiLMiC pro camera application were used on iPhone X to compare bleb images using yellow and white pen-torches as illumination source. Measured bleb area was compared using ImageJ software from the two apps in different illumination settings by charting boxplots and using one-way ANOVA test using R software to establish consistency. Bland-Altman interoperability for repeatability of bleb-area measurements was analyzed by plotting Bland-Altman plots. Signal-to-noise ratio was calculated using ImageJ for native camera images using slit-lamp camera images as reference. Subjective rating of these images was then performed by two experienced ophthalmologists and kappa coefficient was calculated for inter-operator repeatability. Statistical analysis was performed. Results: The measured bleb area from images taken from both apps showed no significant difference, thereby establishing consistency, and Bland-Altman analysis indicated good repeatability and reproducibility. It was noted that SNR was lower for images shot in close illumination as compared to the ones shot in intermediate and distant illumination. Cohen's kappa coefficient was 0.7 for images with distant illumination using white light and 0.65 for images clicked with illumination at an intermediate distance using yellow light, suggesting substantial agreement between the observers. Conclusion: Smartphone photography is a reliable tool for morphological assessment trabeculectomy blebs. Optimal illumination helps achieve results free from digital noise and better delineation of specific morphological features. Intermediate illumination and distant illumination provides much better results in terms of high SNR while avoiding overexposure and clipping of highlight information in the images.